Checklist of the Red Sea Fishes with delineation of the Gulf of Suez, Gulf of Aqaba, endemism and Lessepsian migrants - Golani, Daniel; Fricke, Ronald (Zootaxa, 2018)
The current checklist provides for each species of the Red Sea its records in the Gulf of Suez, Gulf of Aqaba, Red Sea main basin and its general distribution.This new checklist of Red Sea fishes enumerates 1207 species, representing 164 families. Of these, 797 species were recorded from the Gulf of Aqaba and 339 from the Gulf of Suez. The number of species from the Gulf of Suez is evidently lower than the actual number not including 27 Lessepsian (Red Sea) migrants to the Mediterranean that most likely occur in the Gulf. The current list includes 73 species that were newly described for science since the last checklist of 2010. The most specious Osteichthyes families are: Gobiidae (134 species), Labridae (66), Apogonidae (59), Serranidae (including Anthiadinae) (44), Blenniidae (42), Carangidae (38), Muraenidae (36), Pomacentridae (35), Syngnathidae (34), Scorpaenidae (24) and Lutjanidae (23). Among the families of Chondrichthyes, the most specious families are the Carcharhinidae (18 species) and Dasyatidae (11). The total number of endemic species in the Red Sea is 174 species, of these, 34 species are endemic to the Gulf of Aqaba and 8 to the Gulf of Suez.